2020
DOI: 10.1088/1757-899x/744/1/012031
|View full text |Cite
|
Sign up to set email alerts
|

Repair feasibility of SS416 stainless steel via laser aided additive manufacturing with SS410/Inconel625 powders

Abstract: Laser based additive manufacturing technique has been found beneficial in fabricating complex components efficiently. In this paper, laser aided additive manufacturing with powder feeding (LAAM) was used to deposit SS410 or Inconel625 on SS416 substrate. Interfacial microstructure and mechanical properties of the deposited samples are investigated accordingly. Results indicated that deposit without obvious defects can be obtained. The interface samples exhibit comparative or slight lower tensile strength compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Hong et al [ 14 ] used the laser metal deposition (LMD) process to produce an ultrafine TiC particle in order to reinforce Inconel 625 composite parts, which were characterized by a significantly high value of the ultimate tensile strength of 1077.3 MPa, yield strength of 659.3 MPa, and elongation of 20.7%. Weng et al [ 15 ] presented a repair process approach by using the laser aided additive manufacturing with powder flow rate (LAAM) which was successfully applied to deposit the SS410 or Inconel 625 on SS416 substrate. It was shown, that deposited clad exhibited no obvious defects, and the interface samples exhibited comparative or slightly lower ultimate tensile strength in comparison to the SS416 substrate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hong et al [ 14 ] used the laser metal deposition (LMD) process to produce an ultrafine TiC particle in order to reinforce Inconel 625 composite parts, which were characterized by a significantly high value of the ultimate tensile strength of 1077.3 MPa, yield strength of 659.3 MPa, and elongation of 20.7%. Weng et al [ 15 ] presented a repair process approach by using the laser aided additive manufacturing with powder flow rate (LAAM) which was successfully applied to deposit the SS410 or Inconel 625 on SS416 substrate. It was shown, that deposited clad exhibited no obvious defects, and the interface samples exhibited comparative or slightly lower ultimate tensile strength in comparison to the SS416 substrate.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting laser clads are narrower than those in any other process, and as a consequence, the final part does not require either rough or finish machining. The additive nature of the LENS process makes it a more resource-efficient manufacturing technology since less waste is generated in comparison to the subtractive techniques [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Additionally, a less amount of the material could be used for the part repair, which is extremely important in terms of the application of nickel-based alloys.…”
Section: Introductionmentioning
confidence: 99%
“…The increase in wear and hardness was also observed in the SS316/Inconel 718 system [ 17 ]. The FGM produced by using SS410/Inconel 625 materials demonstrated that the depositions were defected free and with good integrity along with the entire interface [ 18 ]. The effect of preheating on FGM was evaluated by using the Inconel 625/Ti6Al4V system, which was shown to promote the formation of thinner and more uniform secondary phases and free of cracks [ 19 ].…”
Section: Introductionmentioning
confidence: 99%